Comunidade que Sustenta a Agricultura (CSA) em São Paulo e Agricultura Solidária (SoLaWi) na Alemanha: construindo indicadores sociais, econômicos e ambientais - Amorim, Joana Ortega de Lima (Universidade Federal de São Carlos, 2018)
Our history shows a shift in the standards of knowledge and technology applied in agriculture. In order to minimize the negative impacts generated by the "green revolution", organic and agroecological production practices also emerge. These include concepts of family agriculture, solidarity economy and local Food systems in Brazil and Europe, and in this context CSA (Community Supported Agriculture) emerges. Studies abour CSA in Brazil are recent and there is a demand for guidelines in pursuit of their establishment as a sustainable option. In this sense we chose the SoLaWi - Solidarich Landwirtschaften (Solidarity Agriculture) in Germany as a parallel for the development of this work. The objective of this work is to analyze the social, economic and environmental aspects that constitute the practices and relations of SoLaWi and CSA, to construct qualitative indicators for each aspect and make a qualitative comparison between SoLaWi and CSA describing the strategies and difficulties, making contributions about the main challenges. The research was qualitative based on the critical communicative methodology and complemented by content analysis and documentary analysis. From the data were created excludent and transformative indicators and it was observed that CSA act by strengthening agroecology in Germany and Brazil. Farmers 'support and empowerment, membership and work opportunity for members, self-management and farmers' autonomy are indicators of transformative social aspects, and this is challenged by the difficulty of member participation and management of volunteer work. The search for economic sustainability is represented in a heterogeneous way due to the different contexts of the communities, especially in what refers to the public policies directed to the local food systems and the solidarity economy. The indicators of the environmental aspects of the communities are the search for biodiversity, soil conservation and health of people and ecosystems, finding limitations in soil conservation and access to land. Future studies on the process of community formation and construction in the context of Latin America are indicated, seeking the training of farmers and members for management and investment in the critical education of members through public policies.
Community Supported Agriculture (CSA) in São Paulo and Solidary Agriculture (SoLaWi) in Germany: building social, economical and ecological indicators
Keywords: Agroecologia; Economia solidária; CSA; Gestão; Organização; Agroecology; Solidary economy; Management; Organization; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; CIENCIAS SOCIAIS APLICADAS::ECONOMIA; CIENCIAS SOCIAIS APLICADAS; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL